"Only questions matter": Philosophy with children from several perspectives - Miloš V. Janković; Ana R. Lipij; Milica R. Sekulović (University of Belgrade, Teacher Education Faculty, 2024)
The paper presents the results of empirical research that examines the reception of the subject Philosophy with Children in the seventh and eighth grades of primary school. The research was conducted in two primary schools in Serbia. It was preceded by the creation of a Manual the scenarios of which, as a template for philosophical research, were formulated in accordance with a problembased approach to teaching philosophy. Some of the research results show that the stimuli that most deeply and permanently encourage reflection are not those close to the pupils, those aimed at their own, familiar, day-to-day experience, but the ones that, by using familiar concepts and situations in discussions, lead to an imaginable perspective of a possible experience (from the experience that is real, one's own or other person's, to the most abstract, normative experience). The skill of organising a philosophy class for children is closely related to the selection of representative stimuli that would enable the formulation of general questions in simpler terms and an articulate discussion of possible answers. Philosophy with children, as a philosophical reflection, should follow, as much as possible, a "dialectical" form, so that the initial question must be general enough to allow the formulation of the criteria for answers, as well as their analysis, revision, and modification. From the introduction of this school subject to its proper use within the framework of institutionalised practice, a lot of time still needs to pass and a lot of work has to be done - above all, teaching and organizational work - for Philosophy with Children to be accepted as a teaching "subject", and even more so for the goals it advocates to be achieved.